The Relationship Between Selected Teaching Approaches and Students’ Performance in English Periodic Exams - Gomez, Aurelio Jr., S.; Sharma, Mani Ram (PPSDP International Journal of Education, 2025)
This study aimed to determine the relationship between teachers’ use of selected teaching approaches and students’ academic performance in English. Employing a quantitative design, data were analyzed using mean, t-test, and Pearson’s r. Results indicated a moderately extensive use of the selected approaches. However, student performance was low overall, with no significant difference by gender. A novel moderate correlation was established, leading to the rejection of the null hypothesis. The primary contribution is the empirical evidence linking specific pedagogical strategies to student outcomes. A key practical implication is the need for targeted teacher training and retooling on effective methods like inquiry-based and analytical approaches. It is recommended that the Department of Education integrate such pedagogical training into its annual review programs to enhance instructional quality and student achievement.